Pengaruh Intellectual Capital dan Good Corporate Governance Terhadap Kualitas Laba (Studi Pada Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia 2021 - 2023) - Marissa Rebecca Gabriella Purba; Wijaya Z, Rico; Safelia, Nela (Jurnal Akuntansi & Keuangan Unja, 2024)
One of the things that companies can do to influence parties related or unrelated to the company is to maintain earnings quality. Earnings quality is information that can be seen and calculated through the company's financial statements, and earnings quality is strongly influenced by several factors, one of which is the company's internal factors. This study aims to determine the relationship between intellectual capital and good corporate governance on the quality of earnings in LQ 45 companies listed on the IDX during 2021 - 2023, with the approach used is a quantitative approach, the population used in this study is 65 companies included in the LQ 45 index for 3 consecutive years. The samples used in this study were 24 companies. The research method used is descriptive research method with a quantitative approach. The variables used in this study are Intellectual Capital (X1), Good Corporate Governance (X2) and Earnings Quality (Y). The analytical tool used is SpSS 26, 2024. The results of this study are that intellectual capital and good corporate governance have no simultaneous effect on earnings quality. However, the component of good corporate governance, namely the joint meeting of the board of commissioners and the board of directors, has a partial effect on earnings quality.